Implementasi Sistem Hybrid Surya–Generator Portabel untuk Meningkatkan Produktivitas Hasil Tangkap Ikan - Ilmirrizki Imaduddin; M. Hasan Basri; Bachtera Indarto; Dicky Mas’Udi Soleh; Moh. Ifan Efendy; Moh. Husnul Lutfi (GUYUB: Journal of Community Engagement, 2026)
This community service program was conducted to address the limited availability of electrical energy on small-scale fishing boats in coastal areas, which often restricts night fishing activities and reduces catch productivity. The program was implemented at the Fish Landing Site (TPI) in Dusun Pesisir, Sumber Anyar Village, Paiton District, Probolinggo Regency, involving local fishermen as the main partners. The objective of this program was to improve energy efficiency and fishing productivity through the implementation of a hybrid solar power system on small fishing vessels. The implementation method consisted of energy needs assessment, system design, equipment installation, technical training for fishermen, and field mentoring followed by performance evaluation. The installed system includes a 550 Wp solar panel, a 12V 100Ah battery, a 1 kW hybrid inverter, and a 2.2 kW portable generator as a backup power source. The results indicate a significant increase in fishing productivity, where the average catch improved from approximately 18 kg to around 33 kg per trip, representing an increase of about 83%. Fishermen’s net income also increased from approximately IDR 525,000 to IDR 1,105,000 per day, or about a 110% improvement. In addition, auxiliary energy consumption became more efficient, with energy cost savings reaching approximately 90% due to reduced dependence on manual battery charging. Overall, the implementation of the hybrid solar power system on small-scale fishing vessels proved effective in improving energy efficiency, fishing productivity, and energy independence for coastal fishing communities.